2023
DOI: 10.3390/catal13020214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Substrate Binding of the Outer Membrane Enzyme OmpT

Abstract: The enzyme OmpT of the outer membrane of Escherichia coli shows proteolytic activity and cleaves peptides and proteins. Using molecular dynamics simulations in a fully hydrated lipid bilayer on a time scale of hundreds of nanoseconds, we draw a detailed atomic picture of substrate recognition in the OmpT-holo enzyme complex. Hydrogen bonds and salt bridges are essential for maintaining the integrity of the active site and play a central role for OmpT in recognizing its substrate. Electrostatic interactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…MD simulations also suggested that the arginine is surrounded by a shell of water molecules during the translocation through the pore. The binding of the peptide substrate ARRA to E. coli OmpT was recently explored by combining AA-MD simulations and umbrella sampling [46]. The translocation of even larger peptides like protamine, a 32 amino-acid-long polycationic peptide, through the CymA channel from K. oxytoca has been studied [47].…”
Section: -Through the Pore: From Channels To Nanoporesmentioning
confidence: 99%
“…MD simulations also suggested that the arginine is surrounded by a shell of water molecules during the translocation through the pore. The binding of the peptide substrate ARRA to E. coli OmpT was recently explored by combining AA-MD simulations and umbrella sampling [46]. The translocation of even larger peptides like protamine, a 32 amino-acid-long polycationic peptide, through the CymA channel from K. oxytoca has been studied [47].…”
Section: -Through the Pore: From Channels To Nanoporesmentioning
confidence: 99%